Wholesalers and the transformation of the “hidden middle” of the aquaculture value chain in Bangladesh - Ali, Hazrat; Belton, Ben; Haque, Mohammad Mahfujul; Hernandez, Ricardo; Khondker, Murshed-E-Jahan; Ignowski, Elizabeth; Reardon, Thomas (Springer, 2025)
The rapid growth of aquaculture in Bangladesh over the past 30 years has been accompanied by a proliferation of wholesalers. Wholesalers are often assumed in academic and public discourse to be exploitative and inefficient: extracting rents rather than driving technological change. This view gives rise to development programs that seek to bypass marketing intermediaries or upgrade their practices. However, there has been little rigorous research on the behavior of wholesalers and its implications for outcomes of value chain performance, including food security. To address this gap, we implemented a statistically representative survey of 229 aquatic food wholesalers in 31 markets in one of Bangladesh’s most important aquaculture zones. We found the following. (1) The wholesale segment of the aquaculture value chain has grown rapidly. (2) Markets are increasingly competitive, with open auctions leading to disintermediation and transparent pricing. (3) Wholesale businesses operate on thin margins. (4) Very little food loss or waste occurs in the farm, wholesale, or retail value chain segments in the study zone. (5) Trading aquaculture products generates substantial employment for men but little for women. Contrary to popular belief, the midstream of the aquaculture value chain in southern Bangladesh is dynamic and efficient. The paper contributes to a growing literature highlighting the contributions that micro, small and medium enterprises (MSMEs) in the “hidden middle” segments of agri-food value chains make to food security.